Fundamentals of materials science and engineering - Pandey, Sumit (SCITUS Academics LLC, 2016)
As early as 1969, a groundbreaking study informed to launch rigorous research activity on the reactivity of photoactivated semiconductor catalysts coined photocatalysis. Staring the decades of development, research activities have come a long way in accomplishments. Currently, articles in different aspects of photocatalysis abound most scientific journals and libraries. The frequent incidence of hazardous chemicals in wastewater produced by anthropogenic and industrial activities is of great concern because these pollutants contaminate lakes, rivers, and underground aquifers; furthermore, currently more pollutants, including traces of contaminants ranging from pharmaceutical drugs, hormones, and sunscreen to pesticides and dyes, are being detected at smaller concentrations in freshwater bodies. In addition, many of these contaminants are recalcitrant compounds, which cannot be degraded by the conventional methods of wastewater treatment; thus, many treated effluents that are considered "safe" for disposal still contain several toxic (bioactive) pollutants.